Investigation of the effectiveness of the method of detection of unauthorized actions in computer networks on the basis of artificial immune systems - Жуков, И. А.; Балакин, С. В. (Problems of Informatization and Management, 2017)
The study of the effectiveness of the method of detecting unauthorized actions in a computernetwork is considered, and information was obtained for the experiment. Options forrecognizing unknown invasions are considered. The general features of behavior of intrusionsin computer networks were revealed and described. The results of implementation andefficiency of the proposed method are presented